PERANCANGAN PACKAGING PAKAIAN RAMAH LINGKUNGAN - Handayani, Arini Nur; Nurhayati, Dyah; Emilda, Nia (Jurusan Seni Rupa ISBI Bandung, 2021)
The design of this environmentally friendly clothing packaging will use Brown kraft paper, which is paper that uses materials that are easily decomposed, can be recycled, and are not harmful to the environment, this paper can use the bleaching process or not. If not bleached, the paper will turn brown. The concept of this work is environmentally friendly clothing packaging. Packaging with illustrations with the theme of water signs or water elements, because it was inspired by the Girl magazine which lists the zodiacs of Pisces, Cancer, and Scorpio. The initial methods used in this work are literature studies, pictorials, and interviews. The design of this work went through several stages of work, starting from the stages of data collection, pictorial studies, sketching, inking process, Layout process and the final stage of finishing.Keywords: packaging, environmentally friendly, clothing——————————————————————————————Perancangan packaging pakaian ramah lingkungan ini akan menggunakan brown craft paper. Brown kraft paper adalah kertas yang menggunakan bahan-bahan yang mudah diurai, bisa didaur ulang, serta tidak berbahaya bagi lingkungan, kertas ini bisa menggunakan proses pemutihan (bleaching) atau tidak. Bila tidak diputihkan maka hasil kertas berwarna coklat. Konsep karya ini yaitu packaging pakaian ramah lingkungan. Packaging dengan gambar ilustrasi yang bertemakan water sign atau elemen air, karena terinspirasi dari majalah Gadis yang mencantumkan zodiak pisces, cancer, dan scorpio. Metode awal yang digunakan dalam pengaryaan ini adalah studi literatur, piktorial, dan wawancara. Perancangan karya ini melewati beberapa tahap pengerjaan, dari mulai tahapan pengumpulan data, studi piktorial, pembuatan sketsa, proses inking, proses Layout dan tahap akhir finishing.Kata Kunci: packaging, ramah lingkungan, pakaian